A Multicenter Pragmatic Interrupted Time Series Analysis of Chlorhexidine Gluconate Bathing in Community Hospital Intensive Care Units. (10th February 2016) - Dicks, Kristen V.; Lofgren, Eric; Lewis, Sarah S.; Moehring, Rebekah W.; Sexton, Daniel J.; Anderson, Deverick J.
Abstract : OBJECTIVE: To determine whether daily chlorhexidine gluconate (CHG) bathing of intensive care unit (ICU) patients leads to a decrease in hospital-acquired infections (HAIs), particularly infections caused by methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus (VRE). DESIGN: Interrupted time series analysis. SETTING: The study included 33 community hospitals participating in the Duke Infection Control Outreach Network from January 2008 through December 2013. PARTICIPANTS: All ICU patients at study hospitals during the study period. METHODS: Of the 33 hospitals, 17 hospitals implemented CHG bathing during the study period, and 16 hospitals that did not perform CHG bathing served as controls. Primary pre-specified outcomes included ICU central-line–associated bloodstream infections (CLABSIs), primary bloodstream infections (BSI), ventilator-associated pneumonia (VAP), and catheter-associated urinary tract infections (CAUTIs). MRSA and VRE HAIs were also evaluated. RESULTS: Chlorhexidine gluconate (CHG) bathing was associated with a significant downward trend in incidence rates of ICU CLABSI (incidence rate ratio [IRR], 0.96; 95% confidence interval [CI], 0.93–0.99), ICU primary BSI (IRR, 0.96; 95% CI, 0.94–0.99), VRE CLABSIs (IRR, 0.97; 95% CI, 0.97–0.98), and all combined VRE infections (IRR, 0.96; 95% CI, 0.93–1.00). No significant trend in MRSA infection incidence rates was identified prior to or following the implementation of CHG bathing. CONCLUSIONS: In this multicenter, real-world analysis of the impact of CHG bathing, hospitals that implemented CHG bathing attained a decrease in ICU CLABSIs, ICU primary BSIs, and VRE CLABSIs. CHG bathing did not affect rates of specific or overall infections due to MRSA. Our findings support daily CHG bathing of ICU patients. Infect Control Hosp Epidemiol 2016;37:791–797